What labelling policy for consumer choice?: The case of genetically modified food in Canada and Europe - Gruère, Guillaume P.; Carter, Colin A.; Farzin, Y. Hossein (Wiley, 2008)
Abstract.  Faced with divergent opinions among consumers on the use of genetically modified (GM) foods, Canada has adopted a voluntary labelling approach for non‐GM foods, whereas the European Union has a mandatory labelling policy for GM foods. Interestingly, both labelling systems have resulted in very little, if any, additional consumer choice. Using an analytical model, we show that the coexistence of GM and non‐GM products at the retail level depends on the labelling policy, consumer perceptions, and the type of product. Although voluntary labelling tends to favour the use of GM products, it is more likely to provide consumer choice.